Answer:
![-\frac{1}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B2%7D)
Step-by-step explanation:
![-\frac{5}{6} +\frac{6}{18}](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B6%7D%20%2B%5Cfrac%7B6%7D%7B18%7D)
reduced
transformed the expression to make it easier
add
reduce
Answer:
The factored form of x^3 -1 will be:
![x^3-1^3=\left(x-1\right)\left(x^2+x+1\right)](https://tex.z-dn.net/?f=x%5E3-1%5E3%3D%5Cleft%28x-1%5Cright%29%5Cleft%28x%5E2%2Bx%2B1%5Cright%29)
Step-by-step explanation:
Given the expression
![x^3-1](https://tex.z-dn.net/?f=x%5E3-1)
Rewrite 1 as 1³
![=x^3-1^3](https://tex.z-dn.net/?f=%3Dx%5E3-1%5E3)
![\mathrm{Apply\:Difference\:of\:Cubes\:Formula:\:}x^3-y^3=\left(x-y\right)\left(x^2+xy+y^2\right)](https://tex.z-dn.net/?f=%5Cmathrm%7BApply%5C%3ADifference%5C%3Aof%5C%3ACubes%5C%3AFormula%3A%5C%3A%7Dx%5E3-y%5E3%3D%5Cleft%28x-y%5Cright%29%5Cleft%28x%5E2%2Bxy%2By%5E2%5Cright%29)
![x^3-1^3=\left(x-1\right)\left(x^2+x+1\right)](https://tex.z-dn.net/?f=x%5E3-1%5E3%3D%5Cleft%28x-1%5Cright%29%5Cleft%28x%5E2%2Bx%2B1%5Cright%29)
![=\left(x-1\right)\left(x^2+x+1\right)](https://tex.z-dn.net/?f=%3D%5Cleft%28x-1%5Cright%29%5Cleft%28x%5E2%2Bx%2B1%5Cright%29)
Thus, the factored form of x^3 -1 will be:
![x^3-1^3=\left(x-1\right)\left(x^2+x+1\right)](https://tex.z-dn.net/?f=x%5E3-1%5E3%3D%5Cleft%28x-1%5Cright%29%5Cleft%28x%5E2%2Bx%2B1%5Cright%29)
16)
(4x + 2) is equal to 150 because they are vertical angles. When two lines intersect, on the opposite sides of the x like these are will be equal to one another. So let’s make them equal to each other.
4x + 2 = 150
Subtract 2
4x = 148
Divide by 4
x = 37
So it will be A
17)
The two angles added up with each other
34 + 146 = 180
Since these two add up to 180 degrees, they would be supplementary angles.
So, H
18)
The two angles will make a 90 degree angle (as shown with the little box formed in the corner)
When angles add up to make 90 degrees, they will be complimentary angles.
So, C.
Here's a graph. Remember that the y intercept crosses the y axis.